2008
DOI: 10.3899/jrheum.080634
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Calcium, Calcitriol, and Alendronate in Corticosteroid-Treated Premenopausal Patients with Systemic Lupus Erythematosus

Abstract: Both calcium alone and calcitriol + calcium preserved lumbar spine BMD in premenopausal patients with SLE taking longterm CS at 2 years, whereas alendronate + calcium led to increases in BMD in lumbar spine and total hip. Premenopausal women taking CS should be considered for osteoporosis prophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 28 publications
0
34
0
1
Order By: Relevance
“…Another 9 studies did not fulfill the inclusion criteria and were therefore excluded. Finally, a total of 9 randomized controlled trials [7,8,1824] were included in our meta-analysis. The literature screen, research selection, and reasons for exclusion were demonstrated in the flowchart (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Another 9 studies did not fulfill the inclusion criteria and were therefore excluded. Finally, a total of 9 randomized controlled trials [7,8,1824] were included in our meta-analysis. The literature screen, research selection, and reasons for exclusion were demonstrated in the flowchart (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The reasons for these conflicting results are unclear and warrant further research on this subject. In general, the reported prevalence of osteoporosis in premenopausal Asian patients with SLE is lower (1.4 -6.1%) than that reported in white patients (4,15), but BMD was significantly lower in premenopausal Asian patients who had had glucocorticoid (GC) treatment than in those who had not (4). In postmenopausal Asian women, the frequency of osteoporosis (48%) is in the same range as whites (2,4).…”
Section: Etiology Of Osteoporosis In Slementioning
confidence: 94%
“…Evidence for efficacy of bisphosphonates in GC-induced osteoporosis has been reported for alendronate, risedronate, ibandronate and zoledronic acid. Alendronate (5 or 10 mg/day) increases BMD, benefitting one in every three individuals treated for 48 weeks, but no reduction in the incidence of vertebral fracture is observed [69,71]. Risedronate (5 mg/ day) may reduce vertebral fractures in up to 70% of patients, benefitting one in every nine individuals treated for 48 weeks [72].…”
Section: Bone Metabolism and Osteoporosismentioning
confidence: 97%
“…In premenopausal SLE patients, a RCT reported maintenance of lumbar spine BMD with calcium carbonate (500 mg/day) and calcitriol (0.25 µg/day) after 2.5 years of therapy [69]. In a meta-analysis of trials, calcium and vitamin D and were shown to significantly improve BMD at the lumbar spine (weighted mean change 2.5) and at the radius in 33% of the patient on GC, but not the BMD at the femur or fracture incidence [70].…”
Section: Bone Metabolism and Osteoporosismentioning
confidence: 99%